Surge testing in low-voltage three-phase motors with random winding: a case study demonstrating its effectiveness. - Gómez, Gonzalo (IEEE, 2024)
There is a lot of experience and regulations linked to dielectric testing of electric motors of 2.3kV or higher for field maintenance, leaving low voltage motors limited to measurements of insulation resistance and winding resistance. However, tests such as the surge test or continuous overvoltage test are powerful tools for field diagnosis of low voltage electric motors, which despite being economical, in many cases represent logistical difficulties for their replacement and large economic losses due to loss of profits. This article presents a case study that shows the usefulness of carrying out impulse tests on low voltage motors, applying the criteria that the regulations recommend for motors of 2.3kV or higher.
Keywords: Ingeniería eléctrica; Motores trifásicos; Baja tensión; Bobinado aleatorio